Measurement of End User Satisfaction Using EUCS Method on Fundraising Administration System of One of Philantrophic Institutions in Indonesia - Nurlaili Rahmi; Rachmadi Indrapraja; Irfandi Buamonabot; Iwan Henri Kusnadi; Kraugusteeliana Kraugusteeliana (Jurnal Sistim Informasi dan Teknologi, 2023)
Abstract This study's objective was to determine the degree to which the end user (a fundraiser) was satisfied with the fundraising administration mobile application system based on content, correctness, format, usability, and timeliness factors. End-user computing satisfaction (EUCS) is the quantitative measuring model researchers employ, and online surveys are distributed to get the necessary information. The researchers opted to include all participants in the population as respondents because 25 regular fundraisers in the Jabodetabek area made up the study's overall population. The data processing programmer utilized is IBM SPSS Statistics 25. The outcomes are the EUCS variables (content, accuracy, format, ease of use, and timeliness), which have a more than 75%% substantial impact on fundraiser satisfaction.